"But, He's So Serious": Framing of Masculinity Among Western Hemisphere Indigenous Peoples in Disney Animated Films. Issue 1 (March 2022) - Luisi, Tim
Few studies to date have examined Indigenous characters in children's media. Stereotyping or omission of underrepresented groups contributes to symbolic annihilation of underrepresented groups, such as Indigenous persons. Through a qualitative textual design, the researcher explored how Western-Hemisphere Indigenous masculinity was framed in five Disney animated films. While Indigenous characters were positively portrayed, the researcher found displays of stereotypes, and an absence of character growth.